Peran Manajemen Sumber Daya Manusia dalam Pengembangan Organisasi - Wesmi, Wesmi; Suatrina, Yenita; Despatriani, Despatriani; Amra, Abhanda (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Human Resource Management (HRM) plays a key role in achieving organizational success. This research aims to delve deeper into the role of HR in the context of modern organizations. The research method used is qualitative analysis of various data sources that include related literature, internal organizational data, and interviews with HR practitioners. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. Research findings show that HR has an important role in employee recruitment and selection, employee development to improve their performance and skills, performance management with evaluations and incentives that encourage productivity, as well as conflict handling and creating a healthy work environment. An effective HR strategy is proven to improve employee performance, achieve organizational goals, and strengthen company competitiveness. The practical implication of the study is that investing in good human resource management can result in a positive impact on organizational growth, employee productivity, and corporate sustainability in the long run